SOCIAL RETURNS FROM DRINKING WATER, SANITATION AND HYGIENE EDUCATION: A Case Study of Two Coastal Villages in Kerala - Pushpangadan, K (Centre for Development Studies-WP333, 2002)
Social returns from investing in water supply, sanitation and hygiene education (WATSANGENE) have been estimated from the UNICEF model of water supply, sanitation and hygiene after modifying it using Sen's commodities and capabilities approach. The various characteristics of the commodity, WATSANGENE, affect significantly the functioning levels of people with respect to poverty, health, longevity, education and quality of environment. Among them, education, longevity and quality of environment have not been evaluated because of the high degree of subjectivity in their measurement leading to wide margin of errors. Hence, only two of them - poverty and health- have been taken up for valuation by case study method and by "with" and "without" project approach. For the case study, two villages from the coastal belt of Kerala inhabited mainly by fishing community were selected. The study clearly shows that the social benefits are underestimated if the travel time is valued by shadow wage rate instead of by the value of energy expended. For example, the value of time saved "with the project" is only 35